2012
DOI: 10.1063/1.4764313
|View full text |Cite
|
Sign up to set email alerts
|

Role of B19′ martensite deformation in stabilizing two-way shape memory behavior in NiTi

Abstract: Deformation of a B19′ martensitic, polycrystalline Ni49.9Ti50.1 (at. %) shape memory alloy and its influence on the magnitude and stability of the ensuing two-way shape memory effect (TWSME) was investigated by combined ex situ mechanical experimentation and in situ neutron diffraction measurements at stress and temperature. The microstructural changes (texture, lattice strains, and phase fractions) during room-temperature deformation and subsequent thermal cycling were captured and compared to the bulk macros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(46 citation statements)
references
References 46 publications
0
46
0
Order By: Relevance
“…Loading below A s or above A f , where the deformation was not fully reversible (e.g., 140 or 260 C test temperatures), is expected to result in internal stress fields that can be caused by a number of sources including dislocation arrays. However, the magnitude of the TWSME was less than 0.2% when initiated through isothermal deformation, which is an order of magnitude less than that observed in binary NiTi under comparable conditions [24].…”
Section: Isothermal Behavior E Tension and Compressionmentioning
confidence: 84%
See 1 more Smart Citation
“…Loading below A s or above A f , where the deformation was not fully reversible (e.g., 140 or 260 C test temperatures), is expected to result in internal stress fields that can be caused by a number of sources including dislocation arrays. However, the magnitude of the TWSME was less than 0.2% when initiated through isothermal deformation, which is an order of magnitude less than that observed in binary NiTi under comparable conditions [24].…”
Section: Isothermal Behavior E Tension and Compressionmentioning
confidence: 84%
“…Since this Ni-rich alloy is a twophase material containing a fine dispersion of second phase precipitates, an increasing externally applied stress is essential in continuing the reorientation and detwinning process. Thus, a distinct plateau is not observed as in some binary, equiatomic NiTi alloys [24]. In addition, this isothermal deformation did not generate any TWSME, likely due to the absence of permanent plastic deformation.…”
Section: Isothermal Behavior E Tension and Compressionmentioning
confidence: 92%
“…The stress can be created by mechanisms such as dislocation arrays resulting from the thermomechanical treatment. The results should be retention of the martensite, some point defects, aligned coherent precipitates or a stabilized stress induced martensite 8,9 . Fine and coherent Ni 4 Ti 3 precipitates formed during aging of Ni-rich NiTi alloys affect the transformation sequence, the transformation temperature and even the mechanical properties of the alloy 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Different wire deflections were reported in literature up to 5 mm; some authors have used deflections between 2 mm and 4 mm and it was stated that although these values were greater than the 5% deflection limit for the span length used, they reproduce the clinical use of the material and are regularly used in the oral environment [3][4][5][6][7][8][9][10]13,14,17,18 . Mallory et al 19 reported that during 5-mm deactivation of all heat activated wires, there was a sharp decline in force production.…”
Section: Mse1mentioning
confidence: 99%
See 1 more Smart Citation